2005
DOI: 10.1016/j.physleta.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Local field effects on the radiative lifetime of emitters in surrounding media: Virtual- or real-cavity model?

Abstract: For emitters embedded in media of various refractive indices, different macroscopic or microscopic theoretical models predict different dependencies of the spontaneous emission lifetime on refractive index. Among those models are the two most promising models: the virtual-cavity model and the real-cavity model. It is a priori not clear which model is more relevant for a given situation. By close analysis of the available experimental results and examining the assumptions underlying the two models, we reach a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Furthermore, the presence of the nanocrystal and the surrounding dielectric sensitively influence the excited state lifetime of atomic dipoles inside, and thereby affect the light-matter coupling strength. For a nanocrystal far in the Rayleigh regime (diameter 20 nm) embedded in a medium, the lifetime is given by [29][30][31][32] x n x n x 2 3 , 4 r r 0…”
Section: Single Nanocrystal Fluorescence Scattering and Lifetimementioning
confidence: 99%
“…Furthermore, the presence of the nanocrystal and the surrounding dielectric sensitively influence the excited state lifetime of atomic dipoles inside, and thereby affect the light-matter coupling strength. For a nanocrystal far in the Rayleigh regime (diameter 20 nm) embedded in a medium, the lifetime is given by [29][30][31][32] x n x n x 2 3 , 4 r r 0…”
Section: Single Nanocrystal Fluorescence Scattering and Lifetimementioning
confidence: 99%
“…These lifetimes, which are somewhat shorter than expected for 5d–4f emission of Eu 2+ at comparable wavelengths, may in part be attributed to defects, however, the main reason is probably the high refractive index n in metal hydrides. It is well‐known that the refractive index or changes of the refractive index of the host medium influence the radiative lifetime , . While the refractive index of metal hydrides is probably 2, the refractive index of many oxides with yellow Eu 2+ emission is rather approximately 1.6 .…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 99%
“…51 Specifically, Duan and Reid recently re-fitted the measured lifetimes for Y 2 O 3 :Eu 3+ nanoparticles immersed in different solvents and showed that the real-cavity model is also applicable for the lifetime dependence on the refractive index, in addition to the widely used virtual-cavity model. 52,53 For comparison, we performed a similar fitting procedure for Eu 3+ : ZnO nanocrystals with the real-cavity model by the following formula 52,53 where n r ) n eff /n np , τ bulk is denoted as the lifetime of bulk Eu 3+ : ZnO, and n eff is the effective index of refraction aforementioned. We re-fitted the experimental data with eq 2.…”
Section: Luminescence Lifetimementioning
confidence: 99%